2005
DOI: 10.1136/thx.2004.036426
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin like activity in bronchoalveolar lavage fluid is suggestive of gastric aspiration in lung allografts

Abstract: Background: A biologically plausible link between gastro-oesophageal reflux (GOR), aspiration, and lung allograft dysfunction has been suggested, but there is no systematic evidence indicating the presence of gastric contents in the lung. We have tested the hypothesis that pepsin, as a marker of aspiration, is detectable in bronchoalveolar lavage (BAL) fluid of allograft recipients who had not reported symptoms of GOR. Methods: Standardised 3660 ml surveillance BAL fluid samples from 13 chronologically sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 14 publications
(13 reference statements)
7
75
1
1
Order By: Relevance
“…The timing of EBC sample collection was selected at random and was irrespective of reflux symptoms; this may influence the ability to fully describe the relationship between gastroesophageal reflux and EBC pepsin. The relationship may also be influenced by the overall EBC pepsin concentrations, which are lower than median levels evident in bronchoalveolar lavage samples (8.3-541 ng/mL) in lung transplant recipients 10,11,14,[40][41][42] and in individuals with pharyngeal reflux (up to 200 ng/mL). 12,36,43 This lower concentration may be at the limit of the detection threshold for the enzyme-linked immunosorbent assay used in this study, which may influence the ability to detect a relationship in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The timing of EBC sample collection was selected at random and was irrespective of reflux symptoms; this may influence the ability to fully describe the relationship between gastroesophageal reflux and EBC pepsin. The relationship may also be influenced by the overall EBC pepsin concentrations, which are lower than median levels evident in bronchoalveolar lavage samples (8.3-541 ng/mL) in lung transplant recipients 10,11,14,[40][41][42] and in individuals with pharyngeal reflux (up to 200 ng/mL). 12,36,43 This lower concentration may be at the limit of the detection threshold for the enzyme-linked immunosorbent assay used in this study, which may influence the ability to detect a relationship in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, this lack of association is consistent with some reports of pepsin present in upper airway samples in individuals with lung disease in whom a diagnosis of gastroesophageal reflux could not be confirmed by esophageal pH monitoring. [9][10][11][12][13]39 The DMS that was used to define gastroesophageal reflux in this study considers not only the frequency of reflux episodes but the position in which they occur (upright or supine) and their duration. 27,40 Short isolated reflux episodes that result in occult aspiration and influence pepsin concentrations in EBC and sputum may be sufficiently infrequent to be detected by esophageal pH monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] Patients who reflux gastric content into the pharynx are at increased risk for aspiration, which can result in pulmonary complications such as chronic cough, asthma, pneumonia, fibrosis, and allograft rejection. [4][5][6] It is estimated that almost 10% of patients with GERD experience pulmonary manifestations; [4] although it is often difficult to effectively gauge the pulmonary consequences of GERD. [7] While pH monitoring is the gold standard for diagnosing GERD clinically, it is not an effective tool for predicting or identifying aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…ROSEN et al [108] recently reported a series of 50 children undergoing bronchoscopy and combined oesophageal pH and impedance monitoring, and found no correlation between the LLMI and reflux events, endoscopic oesophagitis or response to fundoplication. Other BAL markers of aspiration, bile acids and pepsin, have been identified in patients with GERD and lung disease [115][116][117][118], but currently these markers have not been adequately studied as routine diagnostic tests.…”
Section: Bronchiolitis Obliterans In Lung Transplant Recipientsmentioning
confidence: 99%